Clothing purchasing practices of Miriam College sophomore high school students - Dela Torre, Velvet Guevara; Escano, Maria Monica R. (2004.)
Teens represent one of the fastest growing population segments. They yield significant buying power both in their own right and in the context of their family purchasing decisions. (www.cpyu.org) The teenage market is significant, many research organizations are devoting much money and effort in an attempt to aide manufacturers, merchants and service in choosing suitable and profitable items for this rapidly expanding consumer group (Oppenheim, 1965). The primary objective of this study was to examine the clothing purchasing practices Miriam College second year high school students. Specifically, it aimed, to determined the shopping orientation, describe the socio-economic characteristic of the respondents, the factors that influence the purchasing practices such as family, peers and media, and the clothing characteristics of t-shirts and jeans considered when buying clothes. Descriptive method that is concerned with gathering data regarding clothing practices for purchasing of t-shirts and jeans was utilized. Survey questionnaires were distributed to 57 sophomore students of Miriam College. Convenience sampling was used. Respondents who were willing to participate were selected. Descriptive statistics such as frequency distribution and measures of central tendency namely mode and mean were applied to analyze and summarize the results. The gathered data were presented in tables. The major findings of the study were: Majority of the students belong to the high-income families. This is due to the nature occupation of the parents, which is mostly in business and high positions in private company. Nearly all the students save money, more than half of those who save money often pays for their clothing purchases. All have the freedom to select their own clothes. The mothers play a significant role in the clothing purchase practices. Friends may be influential factors but it does not necessarily mean that their clothing choices should be similar to those of their friends. Media influence is minimal. Fit and comfort and style are the clothing characteristics that are most considered by nearly all of the students. The students have different preferences for shops. There was not one shop that came close to 50% of the respondents who go there to buy. The students show awareness in their purchasing decision.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Consumer behavior